The six-voiced secular madrigals of Luca Marenzio - Bennett, K; Bennett, Keith (1978)
﻿ Luca Marenzio has long been acknowledged as one of the greatest masters of the Italian madrigal, yet no collected edition of his works exists: in particular relatively few of the six-voiced madrigals are available in published form, and criticism has tended to concentrate on the five-voiced works. This thesis presents an Edition with Commentary of the six-voiced madrigals published in six books between 1581 and 1595. Two polychoral madrigals and a madrigal by Antonio Bicci also found in those books are included in an Appendix, together with two furtner madrigals included by Phalèse in his 1594 edition of Books I-V, which proved a valuable collative source. The Commentary presents a stylistic study of the madrigals in the Edition and a critical survey of their place in Marenzio's output, together with an editorial commentary and extensive bibliographical material. Following an outline of the madrigal's chief characteristics, Chapter One presents a biographical and critical account of Marenzio's work. Each book of madrigals is considered individually and in relation to his stylistic development. Finally the chapter treats briefly of his influence, with contemporary and historical comment. A stylistic analysis of the music in this Edition follows, considering particularly the relationship between music and text, texture, form, tonality and chromaticism. The poets, forms and principal sources of the texts are then considered. Chapter Four discusses the Edition - sources, notation, tempo, pitch and musica ficta - and concludes with a note on performance. Two Critical Commentaries deal respectively with music and text, the latter providing a comparison between musical and literary versions and listing poets (some newly discovered) and literary sources. The Bibliography lists all published appearances of the six-voiced madrigals and provides a complete reference for the literary sources consulted. The complete texts of the madrigals are given in an Appendix.